PROFIL MANIFESTASI KLINIS DAN LABORATORIUM PASIEN DEMAM TIFOID DI RS PKU BANTUL - Devita, Ninda; Riski, Muhammad Syafiq; Marufi, Rian; Habibah, Ulil Albab (Fakultas Kedokteran, Universitas Palangka Raya, 2023)
Typhoid fever can give various clinical manifestations and laboratoryThis study is a retrospective descriptive study using medical record data. The data collected was clinical manifestations and laboratory then presented in a frequency distribution diagram. A total of 72 typhoid fever patients at PKU Hospital Bantul in 2014-2015 were included as subjects. A 53% of the subjects were women. The mean age was 32 ± 14 years. The main symptoms were fever (99%), gastrointestinal symptoms (91%), headache (37%), muscle aches (11%), and cough (8%). The dominant physical examination found hepatomegaly and dirty tongue (19% and 5%). The main laboratory abnormalities were increased SGOT (46%), SGPT (39%), anemia (26%), and leukopenia (22%) It was concluded, typhoid fever patients often found fever, gastrointestinal symptoms, headache accompanied by anemia, leukopenia, and elevated liver enzymes in laboratory tests.